Retinal detachment after phacoemulsification in high myopia: analysis of 2356 cases - Neuhann, Irmingard M; Neuhann, Thomas F; Heimann, Heinrich; Schmickler, Stefanie; Gerl, Ralf H; Foerster, Michael H (Journal of cataract and refractive surgery, 2008)
To determine the incidence of and risk factors for rhegmatogenous retinal detachment (RD) in highly myopic eyes after cataract surgery. Two ophthalmology centers in Munich and Ahaus, Germany. This retrospective medical chart review comprised 1519 consecutive patients (2356 eyes) with an axial length (AL) greater than 27.0 mm who had planned phacoemulsification and intraocular lens implantation in the capsular bag. In addition, all patients and/or the referring ophthalmologist were contacted regarding the occurrence of RD and laser capsulotomy and the date of occurrence. Follow-up was longer than 24 months in 84% of eyes. Because some cases of RD were questionably related to the preceding cataract surgery, the absolute incidence of postoperative RD was determined as highest (2.2%) and lowest (1.5%). Sex, history of laser capsulotomy, and increasing AL had no statistically significant effect on the rate of RD. The risk for postoperative RD was significantly higher in eyes of younger patients and eyes with preoperative prophylactic treatment for retinal degeneration. The risk for postoperative RD in this study (1.5% to 2.2%) corresponds to the incidence of pseudophakic RD and idiopathic RD in myopia described in the literature. The risk profile for postoperative RD in this series cannot be distinguished from the risk profile for idiopathic RD in myopia of this extent. The true effect of prophylactic treatment of degenerative lesions remains to be elucidated.